Digging Pitch, La Brea, Trinidad - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2009)
Photo of two men loading carts with pitch while another man is digging pitch at La Brea, Trinidad.
Colour: Yellow, Red and Green Hues; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--La Brea; Asphalt industry--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Men--Trinidad and Tobago; Pitch Lake, The (La Brea)